PATIENT-SELECTION PROGRAM TRAINING FOR MENTAL HEALTH CADRES IN DEVELOPING INDEPENDENT BUSINESS FOR THE FAMILY - Algristian, Hafid; Fitriyah, Fifi Khoirul; Fasya, Abdul Hakim Zakkiy; Bistara, Difran Nobel; Putri, Rahmadaniar Aditya; Bariyah, Khadijah Khairul (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
People with severe mental disorder (PSMD; Orang Dengan Gangguan Jiwa, ODGJ) are a vulnerable group of people who experience loss of their rights to life because of their mental limitations, namely the right to work and earn an income independently. In previous activities, there was an opportunity for PSMD to recover through a series of training. To achieve recovery, it is necessary to hold a patient selection program so that patients who take part in the training series are not in the acute phase. Mental health cadres who are close to the community have a big role in determining which PSMD will then take part in entrepreneurship training activities. Therefore, mental health cadres need to deepen their insight into mental disorders and increase their empowerment in patient selection programs for PSMD. This activity aims to increase the understanding of mental health cadres regarding mental disorders and increase their empowerment in implementing patient selection programs for PSMD. The method used was by conducting outreach to mental health cadres regarding the topic of mental disorders as well as providing patient selection program training to mental health cadres. Before counseling and training, a 10-minute pre-test was conducted for the participants, then continued with an outreach and training session as well as questions and answers and discussions for approximately 60 minutes, and at the end a 10-minute post-test was carried out. The results showed an increase in pre-test and post-test data on the topic of mental disorders as well as an increase in empowerment by mental health cadre participants in carrying out patient selection programs. Community service activities regarding patient selection program training for mental health cadres in developing independent businesses for PSMD families in the Gresik district have provided improvements to mental health cadres, namely in the form of increased insight regarding mental disorders and increased empowerment in carrying out patient selection programs for PSMD.